2003
DOI: 10.1183/09031936.03.00085903
|View full text |Cite
|
Sign up to set email alerts
|

Increased vascular endothelial growth factor in acute eosinophilic pneumonia

Abstract: Acute eosinophilic pneumonia (AEP) is associated with the presence of diffuse pulmonary infiltrates on the chest radiograph and an increased number of eosinophils and an elevation of interleukin (IL)-5 levels in bronchoalveolar lavage (BAL) fluid. Vascular endothelial growth factor (VEGF) is a constitutively expressed protein encoded by messenger ribonucleic acid in human eosinophils and is released following stimulation with IL-5. However, the roles of IL-5 and VEGF in the pathogenesis or activity of this dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
(47 reference statements)
4
20
0
1
Order By: Relevance
“…3c). Consistent with another study [34], our result suggested that blood leakage may play a role in the development of AEP. However, the periostin/albumin ratio remained higher in AEP and CEP than in sarcoidosis.…”
Section: Discussionsupporting
confidence: 93%
“…3c). Consistent with another study [34], our result suggested that blood leakage may play a role in the development of AEP. However, the periostin/albumin ratio remained higher in AEP and CEP than in sarcoidosis.…”
Section: Discussionsupporting
confidence: 93%
“…22 The VEGF family is composed of several isotypes, including VEGF-A, VEGF-B, VEGF-C, and VEGF-D, which exist as numerous splice variant isoforms. 15 VEGF 1 eosinophils have been identified in a number of pathological states, including asthma, 13 eosinophilic pneumonia, 23 urticaria, 14 and angioedema. 24 However, to our knowledge, VEGF 1 eosinophils, T cells, and macrophages have not been previously reported in allergen-induced skin inflammation in human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Cationic granule proteins and inflammatory lipid mediators are detectable in the urine of subjects with AEP (136). Vascular endothelial growth factor (VEGF) is elevated in the lungs in AEP, consistent with increased vascular permeability contributing to the pathophysiology of the disease (125). BAL fluid eosinophils in AEP have been noted to have an activated phenotype, with upregulation of HLA-DR and CD69 (135).…”
Section: Aepmentioning
confidence: 99%